THE ROLE OF JOB ANALYSIS IN IMPROVING EMPLOYEE PERFORMANCE IN ORGANIZATIONS - MM Tri Susetyaning Mildawani (Jurnal Ekonomi, 2023)
Job analysis is a systematic process for understanding the duties, responsibilities, and job requirements required in a particular position. This research will explore how the application of job analysis can influence improving employee performance through increasing understanding, suitability and motivation in the workplace. This research aims to investigate the role of job analysis as an effective tool in improving employee performance in an organizational context. The research method used is a qualitative approach with descriptive methods. The results of research on job analysis in an organization show that this process has a crucial role in improving employee performance and managing human resources effectively. Job analysis helps in detailing the duties, responsibilities, skills, and qualifications required in a job, enabling selection of appropriate employees, development of competencies, fair performance appraisal, and improvement of operational efficiency. With a good understanding of their role in the organization, employees become more motivated and engaged in their work, which ultimately contributes to the achievement of organizational goals. Job analysis also helps avoid role conflict and creates alignment between organizational goals and individual roles.